ANALISIS STRATEGI BERSAING DALAM USAHA MODERN FUSION TEA DI ERA DIGITAL (Studi Kasus Menantea Di Kota Bandung) - Laurensia Sri Yubilanti; Tomy Perdana; Dini Rochdiani; Gunardi Judawinata (Universitas Galuh, 2023)
Tea is a drink with a unique taste that has health benefits and is known as a refreshing plant. Modern fushion brand is one way of serving tea by combining new ingredients or drinks with innovative flavors. The digital era is one factor that plays a role in creating innovation and product marketing. For this reason, the use of technology in the form of social media that continues to develop can help companies and become an opportunity for entrepreneurs to run their businesses. Menantea is one of the new companies that experiences problems in its sales, one of which is because there are competitors. Therefore, alternative strategies are needed to deal with business competition. The research method used is qualitative with case study research techniques. The analytical tools used in this study are the IFE matrix, EFE, IE, and QSPM. Based on the results of the IFE and EFE matrices it is known that the Menantea company has strong internal conditions and high external conditions. The results on the IE matrix show that the Menantea company is in growth and building a position in quadrant 1. Thus, companies should carry out alternative strategies according to the results of the QSPM analysis, namely by increasing sales promotion activities using social media digital platforms, expanding product distribution by opening stores in various regions in Indonesia, innovating and developing products, as well as maintaining the company's characteristics and increasing competitive advantage.